Reforming the Students’ Writing Errors in Collocation by Applying Collocation Learning - Kholili, Achmad (Lingual Journal of Language and Culture, 2018)
As a language, English has now spread all over the world and has been known by quite a few people currently. English is known as crucial and salient to learn. The language quite reveals complexities that make some people sometimes give in to continue studying it. It has such as grammar, linguistic terms, and other rules that play a very significant role while applied to daily life. One of the rules that are quite hard to do is combining words within a sentence called as collocation. This paper aims at investigating whether the students at University of Islam Malang have known about collocation. In this study, the researcher conducted a quick survey. The data was collected with an open-questionnaire containing five different sentences in which the students should translate the Indonesian sentence into English correctly using a correct combination of words. The result of the study revealed that the students from University of Islam Malang still have been committing errors in combining words in a sentence; it is due to their little acquaintance with collocation even having no knowledge of it. Since it has happened to the students, by conducting this small research, the researcher expects that the students may learn much more about collocation either from this paper or other resources with regards to collocation learning in English.   Keywords: English, Collocation, Students of University of Islam Malang